Linguistic discrimination in nativa bilingualism students. - Luisa Nataly Aguilar Mescco (2020)
The research work was carried out at the Institute of Public Pedagogical Higher Education of Arequipa, with the purpose of analyzing, firstly, if there is linguistic discrimination towards native bilinguals and, secondly, to know what are the forms of such exclusion. For the operationalization of variables, the following dimensions were considered: native bilingualism (Quechua-Castilian; Aymara-Castilian) and four forms of linguistic discrimination. The type of research is descriptive, ex-post-facto design, developed under the quantitative approach. The survey and a 21-question questionnaire were used to collect information; With these materials we were able to obtain data regarding the different forms of linguistic discrimination towards native Quechua-Aymara bilinguals, within the institution in question. The population is made up of 100% of IESPPA students. The conclusions show the existence of linguistic discrimination towards native bilinguals, because most of them are still unclear about the linguistic varieties and that in our environment the prejudice persists that there is only one standard norm, which is presented as unique and valid and this must be applied in all communicative situations and contexts.